2015
DOI: 10.1002/hipo.22476
|View full text |Cite
|
Sign up to set email alerts
|

A high-fat diet impairs learning that is dependent on the dorsal hippocampus but spares other forms of learning

Abstract: Two experiments were conducted to evaluate the effects of a high-fat diet (HFD) on two tasks that were either dependent on the dorsal hippocampus (DH) or independent of the DH. A total of 80 adult male Sprague Dawley rats were administered either a lard-based HFD (60% of calories from fat) or a control diet (10% of calories from fat) for 8 weeks, and then were trained and tested on either the latent cue preference (LCP) task or the conditioned cue preference (CCP) task in a 3-compartment box apparatus (2 end-c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
2
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(4 citation statements)
references
References 32 publications
2
2
0
Order By: Relevance
“…Interestingly, the current study suggests that a high-fat diet and the resulting metabolic dysfunction preferentially disturb neurogenic processes in the dorsal subregion of the hippocampus, and that this occurs in females only. Our findings of HF diet-induced disruption of neurogenic processes in the dorsal hippocampus are in agreement with studies that have shown that HF diet impairs cognitive function that is dependent on this subregion of the hippocampus (Cordner and Tamashiro, 2015), such as performance on the latent cue preference task or the conditioned cue preference task in a multiplecue environment, while other forms of learning are spared (Stouffer et al, 2015).…”
Section: Sex Differences In the Effects Of High-fat Diet/prediabetes supporting
confidence: 92%
“…Interestingly, the current study suggests that a high-fat diet and the resulting metabolic dysfunction preferentially disturb neurogenic processes in the dorsal subregion of the hippocampus, and that this occurs in females only. Our findings of HF diet-induced disruption of neurogenic processes in the dorsal hippocampus are in agreement with studies that have shown that HF diet impairs cognitive function that is dependent on this subregion of the hippocampus (Cordner and Tamashiro, 2015), such as performance on the latent cue preference task or the conditioned cue preference task in a multiplecue environment, while other forms of learning are spared (Stouffer et al, 2015).…”
Section: Sex Differences In the Effects Of High-fat Diet/prediabetes supporting
confidence: 92%
“…DH appears to be primarily responsible for the cognitive functions of the hippocampus (Moser & Moser, 1998;Sahay & Hen, 2007;Barkus et al, 2010;Fanselow & Dong, 2010), which is consistent with our finding that that genes associated with learning and memory were only impacted in DH. Our findings also add to evidence suggesting that DH is more vulnerable to neuroinflammation and other pathology than VH (Fuster-Matanzo et al, 2011;Stouffer et al, 2015;Dobryakova et al, 2017;Dobryakova et al, 2019;Tournier et al, 2019).…”
Section: Discussionsupporting
confidence: 75%
“…However, despite the moderate reliability and validity of this measure, the YAQ, along with many other food frequency questionnaires, remain the primary method used to quantify diet in research (53), although improvement of these measures represents an important area for future work. Moreover, both animal and human studies suggest that WD exposure impacts hippocampal function, assessed behaviorally (15,28,56). We were unable to look at hippocampal memory impairment, as hippocampal-sensitive memory measures were not obtained.…”
Section: Discussionmentioning
confidence: 95%